Analgesic and Anti- Inflammatory Effect of Zingiber Officinale in Albino Mice - Elzwi, Samia; ALbarasi, Hamida (Scientific Journal of University of Benghazi, 2020)
Zingiber officinale (ginger) is common part of the diet in many parts of the world, Recent research has found ginger to have various pharmacological properties due to a variety of active constituents, including shogoals and gingerols. It is a member of zingiberaceae family originated in Southeast Asia and has been introduced to many parts of the globe where it proliferates in suitable environment. Ginger contain constituents with anti-inflammatory properties. The fresh and dried ginger both contains active 6 – gingerol and gingerdion along with other resinous pungent principle, extracted with n- hexane and methanol that are responsible for inhibition of inflammatory metabolite's production by lipooxygenase and cyclooxyganse. The present paper aimed to determine anti- inflammatory effects of Zingiber officinale extract in experimental animals .The anti-inflammatory activity was assessed by using carrageenan it showed that the plant extract has anti-inflammatory effect in rats by using acetic acid model. The present paper indicated that plant extract has analgesic activity in dose dependent pattern.